2022
DOI: 10.1155/2022/3343244
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Predictor for the Success of 12/14-Fr Ureteral Access Sheath Placement

Abstract: Purpose. Ureteral access sheaths (UAS) are widely used in retrograde intrarenal surgery (RIRS), and this study aimed to develop a model for predicting the success of UAS placement based on computed tomography. Methods. We analyzed the clinical data of 847 patients who received ureteroscopy. Data on patient and stone characteristics and several computed tomography (CT)-based measurements were collected. A nomogram predicting the success of UAS placement was developed and validated using R software. Results. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Identifying patients with evaluated poor or excellent outcomes can guide them in choosing between ureteral stenting or fURS. Some researcher discovered that age, previous same-side procedures, and preoperative stent placement, sex, short medical history, short diameter of the ipsilateral common iliac artery, the shortest axis-base of hydronephrosis, the narrowest thickness of the renal parenchyma, and the narrowest calculus small diameter are signi cant risk factors for the failure of 12/14Fr UAS placement [3,6,7]. Moreover, recently a study revealed that the risk of ureteral injury after UAS (12/14Fr) insertion could be predicted by measuring the inner diameter of the upper ureter [8].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying patients with evaluated poor or excellent outcomes can guide them in choosing between ureteral stenting or fURS. Some researcher discovered that age, previous same-side procedures, and preoperative stent placement, sex, short medical history, short diameter of the ipsilateral common iliac artery, the shortest axis-base of hydronephrosis, the narrowest thickness of the renal parenchyma, and the narrowest calculus small diameter are signi cant risk factors for the failure of 12/14Fr UAS placement [3,6,7]. Moreover, recently a study revealed that the risk of ureteral injury after UAS (12/14Fr) insertion could be predicted by measuring the inner diameter of the upper ureter [8].…”
Section: Introductionmentioning
confidence: 99%